A New Noncovalently Fused‐Ring Electron Acceptor Based on 3, 7‐Dialkyloxybenzo[1, 2‐b:4, 5‐b']dithiophene for Low‐Cost and High‐Performance Organic Solar Cells. Issue 16 (1st April 2022) - Zhang, Xin; Qin, Linqing; Li, Laiyang; Liu, Xingzheng; Wei, Yanan; Huang, Hui
Abstract: The innovation of high‐performance fused‐ring electron acceptors (FREAs) has carried the field of organic solar cells (OSCs) toward a new stage of development. However, due to high synthetic complexity and production costs, FREAs may not be the most promising candidates for future commercialization applications. To address these disadvantages of FREAs, a series of low‐cost acceptors, named as noncovalently FREAs (NFREAs), is successfully constructed by employing the strategy of noncovalently conformational locks. Herein, a novel NFREA (BDTO‐4F) based on 3, 7‐dialkyloxybenzo[1, 2‐ b :4, 5‐ b ′]dithiophene is synthesized and fully characterized. Benefiting from the complementary absorption of the donor and acceptor, balanced charge transport, and favorable film morphology, J52:BDTO‐4F based OSCs afford a satisfied power conversion efficiency of 12.09%, much higher than PBDB‐T:BDTO‐4F‐based devices (8.30%). It is worth mentioning that BDTO‐4F possesses a higher figure‐of‐merit value of 55.65 in comparison with several representative FREAs based on a cost‐efficiency evaluation. This work demonstrates the potential of the novel benzo[1, 2‐ b :4, 5‐ b ″]dithiophene derivative for constructing low‐cost and high‐performance NFREAs, providing a valuable insight on the materials design. Abstract : Present herein is the first case that 3, 7‐dialkyloxybenzo[1, 2‐ b :4, 5‐ b ′]dithiophene is employed in the field of organic solar cells. Thus, a new small‐molecule material incorporating S···O noncovalently conformational locks is successfully developed as a promising noncovalently fused‐ring electron acceptor, which shows a considerable power conversion efficiency of 12.09%.